THE ASSOCIATION BETWEEN SOCIODEMOGRAPHIC FACTORS AND TEACHERS’ GUIDANCE TOWARDS STUDENTS’ ADVERSITY QUOTIENT - Listiawati, Nur; Sebayang, Susy K (International Journal of Education, 2019)
This paper aims to report results of research on the association between sociodemographic indicators and teachers’ efforts to help students cope with problems and help build students’ Adversity Quotient. A questionnaire in the form of self-report inventory was distributed to 102 fourth, fifth, and sixth grade students of A- and C-accredited primary schools in Bantul Regency, Yogyakarta, Indonesia. Multiple regression and inductive reasoning were used for analysis. FGDs with teachers were conducted in order to explore teachers’ efforts in helping improve students’ adversity quotient. Research results showed that students who were middle child had significantly lower AQ compared to those of first-born or earlier-born child, while sixth-graders had significantly higher AQ scores compared to fourth graders, and children whose fathers were skilled workers had greater odds of having high AQ. Teachers had already done some LEAD sequence, but had not guided students to explore and analyze the problem by themselves. The results have some implications for the education policy to integrate religious teachings into the curriculum that can facilitate the improvement of students’ Adversity Quotient.